Operando investigation of the synergistic effect of electric field treatment and copper for bacteria inactivation - Mourin Jarin; Ting Wang; Xing Xie (Nature Communications, 2024)
Abstract As the overuse of chemicals in our disinfection processes becomes an ever-growing concern, alternative approaches to reduce and replace the usage of chemicals is warranted. Electric field treatment has shown promising potential to have synergistic effects with standard chemical-based methods as they both target the cell membrane specifically. In this study, we use a lab-on-a-chip device to understand, observe, and quantify the synergistic effect between electric field treatment and copper inactivation. Observations in situ, and at a single cell level, ensure us that the combined approach has an enhancement effect leading more bacteria to be weakened by electric field treatment and susceptible to inactivation by copper ion permeation. The synergistic effects of electric field treatment and copper can be visually concluded here, enabling the further study of this technology to optimally develop, mature, and scale for its various applications in the future.